SEQUENCE ANALYSIS OF HOT SPOT REGIONS OF SPIKE AND RNA‑DEPENDENT‑RNA POLYMERASE (RDRP) GENES OF SARS-COV-2 IN KERMAN, IRAN - Nasir; Ramin; Amin; Jamal (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Background: Mutations in the SARS-CoV-2 genome might influence pathogenicity, transmission rate, and evasion of the host immune system. Therefore, the purpose of this study was to assess the genetic alteration in the receptor binding domain (RBD) of the spike and putative RNA binding site of the RdRp genes of SARS-CoV-2. Materials and Method: In this cross-sectional study, 45 confirmed COVID-19 patients using qRT-PCR were included and divided into mild, severe, and critical groups based on the severity of the disease. RNA was extracted from nasopharyngeal swab samples using a commercial kit. RT-PCR was performed to amplify the target sequences of the spike and RdRp genes and sequenced them by the Sanger method. Clustal OMEGA, MEGA 11 software, I-mutant tools, and SWISS-MODEL and HDOCK web servers were used for bioinformatics analyses. Results: The mean age of the patients was 50.68±2.73. The results showed that four of six mutations (L452R, T478K, N501Y, and D614G) in RBD and three of eight in the putative RNA binding site (P214L, E1084D, V1883T) were missense. In the putative RNA binding site, another deletion was discovered. Among missense mutations, N501Y and V1883T were responsible for increasing structural stability, and the others were responsible for decreasing it. The various homology models designed showed that these homologies were like the Wuhan model. The molecular docking analysis revealed that the T478K mutation in RBD had the highest binding affinity. In addition, 35 RBD samples (89.7%) and 33 putative RNA binding site samples (84.6%) were similar to the Delta variant. Conclusion: Our results indicated that double mutations (T478K and N501Y) in the S protein might increase the binding affinity of SARS-CoV-2 to human ACE2 compared to the wild type (WT) strain. Moreover, variations in the spike and RdRp genes might influence the stability of encoded proteins.